2008
DOI: 10.1096/fj.08-116863
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of a human insulin‐like growth factor 1 promoter P1 variation

Abstract: Insulin-like growth factor 1 (IGF1) exerts important endocrine and paracrine functions in the cardiovascular system. We identified the common variant -1411C>T in the IGF1 upstream promoter P1, located within several overlapping transcription factor binding sites. Using transient transfection assays, we identified this site as a functional enhancer. The T allele-carrying enhancer, compared with the C allelic portion, exerts significantly reduced or even abrogated activity, respectively, in SaOs-2 and HepG2 (all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…We conclude that transcriptional activators other than C/EBPb could contribute to IGF-1 transcriptional regulation, depending on tumour-imposed stress conditions. Indeed, several other transcription factors were shown to activate IGF-1 transcription in diverse cell types, including Stat5 in hepatocytes and putatively in DCs [47][48][49] , C/EBPd in osteoblasts and putatively DCs 50 , and IRF8 in hepatocytes 51 . When IGF-1 and other potentially B-cell growth-promoting cytokines were tested in a DC-independent cell culture, gain of viability between the Em-Myc lymphoma B-cell clones varied substantially.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that transcriptional activators other than C/EBPb could contribute to IGF-1 transcriptional regulation, depending on tumour-imposed stress conditions. Indeed, several other transcription factors were shown to activate IGF-1 transcription in diverse cell types, including Stat5 in hepatocytes and putatively in DCs [47][48][49] , C/EBPd in osteoblasts and putatively DCs 50 , and IRF8 in hepatocytes 51 . When IGF-1 and other potentially B-cell growth-promoting cytokines were tested in a DC-independent cell culture, gain of viability between the Em-Myc lymphoma B-cell clones varied substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Cis-active elements exert transcriptional activity by interaction with TFs that assemble at the promoter as modules, 25 the composition of an individual module being cell type-and context-specific. For OPG, we propose a hypothetical transcriptional module ( Figure 6B): (I) Sp1, NF-1, and NF-B bind to the MolHap portion, and interact with Egr1 (Ϫ159T allele) to cooperatively stimulate transcription; (II) The Ϫ159C allele leads to a loss of the TFBS for Egr1, the transcriptional module is altered and transcriptional activity is decreased; (III) Truncation leads to a loss of TFBS for Sp1, NF-1, and NFB, whereas Egr1 alone seems to act as a repressor; (IV) Introduction of the Ϫ159C allele into the truncated constructs results in a partial restoration of transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a C/EBPD transcription activation complex binds exclusively to the C allele of rs35767 to activate IGF1 promoter activity33. To test whether the C allele is responsible for the promoter activation ability of the 125-bp segment and the length effect of the microsatellite, we mutated haplotype C-T-T to haplotype T-T-T in all of the promoter fragments and examined for their gradational transactivation properties as a function of microsatellite repeat length.…”
Section: Resultsmentioning
confidence: 99%
“…A transcriptional activator C/EBPD complex binds exclusively to the C allele of this SNP and activates promoter transcriptional activity33. Moreover, genome-wide association studies and epidemiologic studies have consistently demonstrated a significant association between this SNP and circulating IGF1 levels or IGF1-related phenotypes4142434445.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation